Characterizing Awareness of Pre-Exposure Prophylaxis for HIV Prevention in Manila and Cebu, Philippines: Web-Based Survey of Filipino Cisgender Men Who Have Sex With Men - Arjee Restar; Anthony Surace; Alexander Adia; William Goedel; Adedotun Ogunbajo; Harry Jin; Alberto Edeza; Laufred Hernandez; Susan Cu-Uvin; Don Operario (JMIR Publications, 2022)
BackgroundThe Philippines is experiencing an HIV crisis and is considering implementing pre-exposure prophylaxis (PrEP) as a national public health strategy for HIV prevention for cisgender men who have sex with men (cis-MSM). However, critical information on the awareness of PrEP among cis-MSM is needed to roll out this public health initiative. ObjectiveThis study aims to assess PrEP awareness and related correlates (ie, sociodemographic variables, social factors, and health care access and use) among Filipino cis-MSM. MethodsWe conducted a web-based survey with Filipino cis-MSM (n=179) residing in the cities of Manila and Cebu, Philippines. Multivariable analysis procedures were performed to examine the factors associated with PrEP awareness. ResultsOur sample demonstrated high awareness (134/179, 74.9%) and interest (159/179, 88.8%) in taking PrEP. The adjusted model showed that greater odds of PrEP awareness were associated with having a college education or higher versus a high school education or lower (adjusted odds ratio [aOR] 7.30, 95% CI 1.01-52.47), earning between PHP 10,000 (US $198.6) and PHP 20,000 (US $397.2) versus <PHP 10,000 (US $198.60; aOR 9.32, 95% CI 1.41-6.22), having had a prior HIV test (aOR 6.06, 95% CI 1.20-13.55), having high HIV knowledge (aOR 3.50, 95% CI 1.11-10.98), and having friends who discussed PrEP (aOR 11.17, 95% CI 2.73-14.5). ConclusionsOur findings demonstrate that Filipino cis-MSM are aware of and interested in taking PrEP, but there is currently an unmet need for such biomedical HIV prevention technologies among this population. Incorporating PrEP education into routine HIV screening and leveraging cis-MSM social networks may be useful in optimizing potential PrEP implementation in the Philippines.